2018
DOI: 10.1002/jat.3721
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure to carbon nanoparticles induced methylome remodeling and gene expression in zebrafish heart

Abstract: Growing black carbon (BC) emission has become one of the major urgent environmental issues facing human beings. Usually, BC or BC‐containing carbon nanoparticles (CNPs) were recognized as non‐directly toxic components of atmospheric particulate matter. However, epidemiology studies have provided much evidence of the associations of exposure of particulate‐containing carbon particles with cardiovascular diseases. There are still no related studies to support the epidemiological conclusions. Hence, in this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 41 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…PM 2.5 was only reported to cause oxidative damage to DNA in humans [ 237 ]. However, a recent study that exposing zebra to carbon nanoparticles showed a disturbance on DNA methylation of the genes in heart tissue, revealing the unregulated gene expression caused by PM [ 248 ].…”
Section: Health Effects Associated With Pm Invasionmentioning
confidence: 99%
“…PM 2.5 was only reported to cause oxidative damage to DNA in humans [ 237 ]. However, a recent study that exposing zebra to carbon nanoparticles showed a disturbance on DNA methylation of the genes in heart tissue, revealing the unregulated gene expression caused by PM [ 248 ].…”
Section: Health Effects Associated With Pm Invasionmentioning
confidence: 99%
“…27 Indeed, it is increasingly clear that disruption of normal DNAm patterning during early cardiovascular development may have long-term, adverse health consequences. 28,29 Recent studies demonstrate that DNAm in the heart is altered in disease states, 28,29 after obesogenic diet exposure, 28 and with toxicant exposures, 30,31 suggesting that this modification may play a key role in CVD pathogenesis. Despite this, the effects of early-life phthalate exposure on cardiac DNAm have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Like nanogenotoxicity, the assessment of the epigenetic toxicity of nanomaterials is mostly based on in vitro followed by in vivo (mice or rats) models ( Figure 6 ). Besides these models, DNA methylation studies were also reported in ecotoxicology model species (such as white worms [ 144 ] and zebrafish [ 145 , 146 ]), while histone modification [ 147 ] and ncRNA (lncRNA and miRNA) were mainly reported in nanomaterial-exposed roundworms ( C. elegans ) ( Figure 6 ). In the epigenetic study design, one must consider the development of a long-term impact with multigenerational or transgenerational effects, preferably with alternative in vivo models (e.g., zebrafish, drosophila, and C. elegans ) [ 147 ] to reduce animal use.…”
Section: Genotoxicity and Epigeneticsmentioning
confidence: 99%